Análise de potenciais áreas de risco à poluição do Aquífero Bauru na zona urbana de Araguari, MG - Carolina Vieira de Andrade (2016)
It is common sense that everybody needs access to water to live and, increasingly, groundwater has been used as an alternative for human use. An example is Araguari city (municipality localized in western Minas Gerais state, Brazil) that uses the Bauru aquifer's waters as the main source of drinking water supply. Work's objective were to study the Bauru Aquifer's vulnerability and risk in Araguari's urban area and consisted of an update of the vulnerability map using the DRASTIC and GOD methods. Also, the present study provided a risk analysis for potential polluting using the land use map. This work present two scenarios to assess the potential risk of pollution, the first was composed by vulnerability obtained by the DRASTIC model associated with the current land occupation map; the second scenario was the vulnerability by the DRASTIC model associated with land occupation map based on Araguari's Master Plan. To obtain vulnerability maps and scenarios, GIS tools and Decision Support Systems were employed.